Factors associated with the occurrence of dengue epidemics in Brazil: a systematic review - Selma Costa de Sousa; Mariângela Carneiro; Álvaro Eduardo Eiras; Juliana Maria Trindade Bezerra; David Soeiro Barbosa1 (Pan American Health Organization, 2021)
Objective. To identify and describe broadly the factors related to the occurrence of dengue epidemics in Brazil. Methods. Systematic review of studies published in Medline, Lilacs, PubMed, Cochrane, BVS, Web of Science, Scopus, and thesis and dissertations databases using descriptors cataloged in DeCs and MeSH on dengue and factors associated with the occurrence of epidemics, published from 2008 to 2018. Results. Thirty-five studies carried out in the country were selected. The epidemics recorded in Brazil were associated and/or correlated with multiple factors such as environment, socioeconomic conditions, climate, and aspects related to the vector, among others. Conclusions. Dengue epidemics are complex and multifactorial. The continuity of the vector control actions was found to be relevant to the reduction of Aedes aegypti and for disease control. To contain the spread of the disease, effective measures are needed in all sectors, including health, education, economy, population, business, and government. Actions for the early detection of cases of the disease can prevent new outbreaks of epidemics.